Dose Variation Profiles of Small Fields with a 10 MV Photon Beam (Global Journal of Science Frontier Research, 2023)
Radiotherapy is an important treatment form to care of patients with different types of cancer and improvement quality of life Radiotherapy is a treatment of carcinogenic tumors using ionising radiation and the refinement of techniques in radiotherapy treatments are programmed to salvage of healthy tissues The small dimensions in modern advanced radiotherapy treatments have employed in differents hospitals These fields have differents characteristics for nonestablishment in the conditions to traditional dosimetry protocols The obtained profiles permissible to check out disturbances in the exposures considering the differences in the dosimetry of small fields and the impacts to local dose deposition In this work the dose distribution of an X-ray beam was recorded using a solid water phantom This phantom was irradiated using small fields with 1x1 2x2 3x3 and 5x5 cm The 10 MV X-ray beam was generated in a linear accelerator model Synergy Platform from the manufacturer Elekta and radiochromic film sheets were used to record dose profiles inside a solid water phantom
Keywords: dose profile; radiotherapy; small fields; solid water phantom